Chimamanda Ngozi Adichie, una Scheherazade africana1 Reseña. Adichie, C. N. (2018). El peligro de la historia única. Barcelona: Penguin Random House. - Romo, Mateo (Cultura Latinoamericana, 2021)
reseña